Phase I/II trial testing safety and immunogenicity of the multipeptide IMA950/poly-ICLC vaccine in newly diagnosed adult malignant astrocytoma patients. Issue 7 (3rd May 2019) - Migliorini, Denis; Dutoit, Valérie; Allard, Mathilde; Grandjean Hallez, Nicole; Marinari, Eliana; Widmer, Valérie; Philippin, Géraldine; Corlazzoli, Francesca; Gustave, Robin; Kreutzfeldt, Mario; Blazek, Nathalie; Wasem, Joëlle; et al.
Abstract: Background: Peptide vaccines offer the opportunity to elicit glioma-specific T cells with tumor killing ability. Using antigens eluted from the surface of glioblastoma samples, we designed a phase I/II study to test safety and immunogenicity of the IMA950 multipeptide vaccine adjuvanted with poly-ICLC (polyinosinic-polycytidylic acid stabilized with polylysine and carboxymethylcellulose) in human leukocyte antigen A2+ glioma patients. Methods: Adult patients with newly diagnosed glioblastoma ( n = 16) and grade III astrocytoma ( n = 3) were treated with radiochemotherapy followed by IMA950/poly-ICLC vaccination. The first 6 patients received IMA950 (9 major histocompatibility complex [MHC] class I and 2 MHC class II peptides) intradermally and poly-ICLC intramuscularly (i.m.). After protocol amendment, IMA950 and poly-ICLC were mixed and injected subcutaneously ( n = 7) or i.m. ( n = 6). Primary endpoints were safety and immunogenicity. Secondary endpoints were overall survival, progression-free survival at 6 and 9 months, and vaccine-specific peripheral cluster of differentiation (CD)4 and CD8 T-cell responses. Results: The IMA950/poly-ICLC vaccine was safe and well tolerated. Four patients presented cerebral edema with rapid recovery. For the first 6 patients, vaccine-induced CD8 T-cell responses were restricted to a single peptide and CD4 responses were absent. After optimization of vaccine formulation, we observed multipeptide CD8 and sustained T helper 1 CD4 T-cell responses. For the entire cohort, CD8 T-cell responses to a single or multiple peptides were observed in 63.2% and 36.8% of patients, respectively. Median overall survival was 19 months for glioblastoma patients. Conclusion: We provide, in a clinical trial, using cell surface-presented antigens, insights into optimization of vaccines generating effector T cells for glioma patients. Trial registration: Clinicaltrials.gov NCT01920191.